A Cathepsin‐L is required for invasive behavior during Air Sac Primordium development inDrosophila melanogaster. Issue 20 (2nd September 2015) - Dong, Qian; Brenneman, Breanna; Fields, Christopher; Srivastava, Ajay
Abstract : The Drosophila Air Sac Primordium (ASP) has emerged as an important structure where cellular, genetic and molecular events responsible for invasive behavior and branching morphogenesis can be studied. In this report we present data which demonstrate that a Cathepsin‐L encoded by the gene CP1 in Drosophila is necessary for invasive behavior during ASP development. We find that CP1 is expressed in ASP and knockdown of CP1 results in suppression of migratory and invasive behavior observed during ASP development. We further show that CP1 possibly regulates invasive behavior by promoting degradation of Basement Membrane. Our data provide clues to the possible role of Cathepsin L in human lung development and tumor invasion, especially, given the similarities between human lung and Drosophila ASP development. Abstract : Cysteine Protease‐1 (CP1) is expressed in Air Sac Primordium (ASP). CP1 is necessary for ASP invasive and migratory behavior. Overexpression of CP1 results in the degradation of Basement Membrane. ASP tip cells lose junctional contacts and undergo a partial Epithelial Mesenchymal Transition.